PERTANGGUNG JAWABAN PERBANKAN DALAM PELANGGARAN PRINSIP KEHATI-HATIAN TERHADAP NASABAH BANK KONVENSIONAL PADA PEMBLOKIRAN REKENING SECARA SEPIHAK - Wilson Petrus Manalu (Fakultas Hukum Universitas Kristen Indonesia, 2020)
the funds to do many types of business activities in order to obtain profit. That profit will be usedto operational capital. Indonesia as a country that has many types of banking institution and issupported by a number of people who use banking’s service. That excellence makes the drivingforces of the people’s economy. There are four banking principles applied in the Indonesianbanking system, one of which is the principle of bank prudence. The principle of bank prudence isa principle in which banks must always be careful in carrying out and conducting their dutiesand functions in order to continue to get the trust of the community. The public’s principles is animportant thing for banking. If the public’s principle is not well applied, the banking will notgrow up and loose much profit and of course the country where that banking built will bedisturbed. However, if we see between banking and customers do not really have a balanceposition. Banking always request their customers to do all rules they make, banking should takecustomer’s position as a very important one because without the customers the bank will notgrow up and go bankrupt.